Exploring the Determinants of CEO Compensation in the US Non-profit Organizations - Wang, Yutong (2020)
This paper examines the impact of performance, governance and chief executive officer (CEO) characteristics on CEO compensation in US non-profit organizations for the whole sample, the health sector and the education sector separately. For the whole sample, after considering the sectoral factors, the result indicates that neither the performance nor governance has an influence on CEO compensation and the tenure of CEO is positively related to the CEO compensation. The findings question the agency theory and consider the application of the stewardship theory in the non-profit context. After deleting the impact of sectors on CEO compensation, for the education sector, which is a traditional non-profit organization type, the result is nearly the same with the whole sample. For the health sector, which is more like the for-profit organization, the governance quality is negatively related with the CEO compensation and the fundraising ration is positively associated the CEO compensation, following the agency theory instead.